Analisa Kinerja Operasional dan Temperature Terhadap Life Time Transformator 370 MVA - Setio Pambudi (Publikasi Indonesia, 2023)
Transformers are very important electrical equipment in the electricity system. Transformers function to increase and decrease the voltage of the electrical assembly system and distribution system. With the temperature conditions in Indonesia, the average temperature in the power plant uses transformer insulation oil cooling. The loading on the power plant transformer always changes depending on the load management center. At the time of loading, there will be current flowing into the transformer coil resulting in increased transformer temperature. Too hot temperatures will cause damage to the transformer insulation and will result in a reduction in the useful life of the transformer itself. This research is carried out observation and analysis by knowing the performance of the transformer in the duration of 24 hours of normal operation by comparing the effect of operating temperature when the load changes, environmental temperature and hotspot temperature. The change in temperature increase that occurs in the transformer is influenced by several factors, including the individual transformer and the temperature of the environment where the transformer is operated. The individual temperature of the transformer is caused by the amount of loading borne by the transformer so that the current flowing in the transformer winding will be higher, the current that continues to increase will cause the transformer winding. A very high temperature in the winding will cause damage to the insulation and the temperature rise can change the insulating properties of the transformer oil which results in the value of the insulating oil decreasing and the decrease in the ability of the insulation level affects the useful life of the transformer. Another factor of increasing transformer temperature is from ambient temperature. With the conditions under which the transformer is operated and the tropical climate conditions in Indonesia which are quite high, this can cause an increase in transformer temperature.